Unveiling dynamics of language visibility and vitality in café menus near Labrang Monastery - He, Min; Chen, Shengnan (Frontiers in Psychology, 2024)
This study explores the dynamics of linguistic landscapes (LL) in the commercial tourist district near Labrang Monastery by analyzing the use of Tibetan, Mandarin, and English on café menus. Traditionally, LL research has focused on language visibility as an indicator of vitality, overlooking contextual complexities. We challenge this approach by considering geocultural contexts, instigators' language proficiency, and intended audience.Our findings underscore the nuanced interplay of these factors in shaping language representation and vitality. By advocating for a holistic LL research approach, integrating qualitative insights with quantitative data, this study contributes to a deeper understanding of LL dynamics. Beyond mere visibility, languages on café menus serve as symbolic markers of ethnic identity and reflect the functions they assume within the speech community, offering insights into language vitality across different usage contexts. This research enriches scholarly discourse on LL, particularly within the Chinese context, by emphasizing the multifaceted nature of language presence and its vitality.